A reforma tributária como alternativa de simplificação do sistema tributário – revisão sistemática de literatura - Rocha, Bruno Fernandes (2023)
Tax reform highlights the need to simplify the tax system. This reform focuses on Value Added Tax (VAT), describing it as a necessary measure to simplify the system. The objective was to identify the possible impacts that would be caused by tax reforms on the national tax system, through a systematic literature review. The systematic literature review methodology consisted of searching for articles related to tax reform in Brazil, from 2013 to 2023, using the databases “Periódicos CAPES”, “Directory of Open Access Journals (DOAJ)” and “Gale Academic OneFile”, complying with the inclusion and exclusion criteria. Different perspectives are presented in the studies that make up the research, from the analysis of the tax burden for companies taxed by presumed profit to the perception of students, teachers and professionals regarding the implementation of VAT. Tax planning is presented as a crucial tool for effective tax management, with an emphasis on tax avoidance as a legal practice to reduce the tax burden. The research demonstrated the complexity of the national tax system, attributing it to the multifaceted nature of contemporary economic activities and the intricate legal structure. Tax reform is of great social and economic relevance, pointing to the need to simplify the system. The results provide information that allows us to understand the possible social and economic effects of the changes proposed by the tax reform.